Hoe is de wereld eraan toe : 1990 - Brown, Lester R.; Flavin, Christopher; Postel, Sandra; Starke, Linda; Liefrink, Jos (Antwerpen : Standaard Uitgeverij, 1990)
Aanwinst van De Batselier, Norbert
Oorspronkelijke titel : "State of the World 1990"
Nederlands
Monografie